Specific Activities of Natural Radionuclides and Annual Effective Dose Due to the Intake of Some Types of Children Powdered Milk Available in Baghdad Markets - Baghdad Science Journal (مجلة بغداد للعلوم, 2017)
In this research the specific activity of natural radionuclides 226Ra, 232Th and 40K were determined by sodium iodide enhanced by thallium NaI(TI) detector and assessed the annual effective dose in Dielac 1 and 2 and Nactalia 1 and 2 for children of less than 1 year which are available in Baghdad markets. The specific activity of 40K has the greater value in all the types which is in the range of allowed levels globally that suggested by UNSCEAR. The mean value of annual effective doses were 2.92, 4.005 and 1.6325 mSv/y for 226Ra, 232Th and 40K respectively.